2023
DOI: 10.1002/adem.202201463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti2SnC MAX Phase on Microstructure, Mechanical, Electrical, and Wear Properties of Stir‐Extruded Copper Matrix Composite

Abstract: Herein, the effect of Ti2SnC MAX phase reinforcement and friction stir back extrusion (FSBE) parameters on the microstructure, mechanical, electrical, and tribological behavior of Cu‐Ti2SnC composite is investigated. The results indicate that, depending on the rotational speed of the extrusion process, an equiaxed grain microstructure with a uniform distribution of reinforcing particles is formed after the extrusion process. Comparing the extruded samples to the unprocessed samples reveals a larger grain size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…By increasing the rotation speed from 400 to 1000 rev min −1 , it is observed that the difference in the distribution of particles in the central and surface areas of the composite wire decreases, and it can see a more uniform distribution of the reinforcing particles. Meanwhile, in the lower addition of Ti 2 SnC particles (5 vol.-% of the reinforcing phase) [26], no significant difference in the distribution was observed in the surface and central areas of the composite wire, indicating that increasing the Ti 2 SnC reinforcing phase strongly influenced the flowability of the mixture of copper powder and the Ti 2 SnC reinforcing phase, causing a material flow gradient in the surface and central areas. Another noteworthy point is the difference in grain size in the central and surface areas of the extruded wires.…”
Section: Resultsmentioning
confidence: 99%
“…By increasing the rotation speed from 400 to 1000 rev min −1 , it is observed that the difference in the distribution of particles in the central and surface areas of the composite wire decreases, and it can see a more uniform distribution of the reinforcing particles. Meanwhile, in the lower addition of Ti 2 SnC particles (5 vol.-% of the reinforcing phase) [26], no significant difference in the distribution was observed in the surface and central areas of the composite wire, indicating that increasing the Ti 2 SnC reinforcing phase strongly influenced the flowability of the mixture of copper powder and the Ti 2 SnC reinforcing phase, causing a material flow gradient in the surface and central areas. Another noteworthy point is the difference in grain size in the central and surface areas of the extruded wires.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, extensive work has been done to explore the preparation process and the conduction and mechanical properties of Cu-MAX composites. The results show that the MAX phases are efficient to strengthen the mechanical properties of Cu matrix composites, without a drastic reduction of their conductivity [166][167][168]. Nevertheless, the research of Cu-MAX composites is still in its infancy, and more in-depth research and exploration are urgently needed.…”
Section: ) Hasselman-johnson Modelmentioning
confidence: 99%